Human solidarity in Western political thought A study in (concept, stages and political ideas) (قضايا سياسية, 2023)
Global challenges, environmental disasters and health risks necessitated the activation and implementation of the generation of human solidarity rights. (To find out the need that prompted contemporary Western political thought to research the concept of human solidarity, and What are the political ideas discussed, and Was it inclusive of all rights(.I argue (that the need that prompted contemporary Western political thought to research In the concept of human solidarity, It manifested itself in a set of factors and challenges that faced individuals, societies and countries, after which one of the claimed human rights, In addition to other rights that everyone should enjoy, contemporary Western political thought circulated a series of political ideas in its search for the concept of human solidarity associated with multiple human rights). In conclusion, we found: (The relationship of the impact of human solidarity with power in its various forms to achieve its goals, there is no guarantee for the idea of human solidarity in the long term if it is not linked to the political field of life(.